The ingestion of combined carbohydrates does not alter metabolic responses or performance capacity during soccer-specific exercise in the heat compared to ingestion of a single carbohydrate - Clarke, N. D.; Campbell, I. T.; Drust, B.; Evans, L.; Reilly, T.; Maclaren, D. P. M. (Journal of Sports Sciences, 2012)
This study was designed to investigate the effect of ingesting a glucose plus fructose solution on the metabolic responses to soccer-specific exercise in the heat and the impact on subsequent exercise capacity. Eleven male soccer players performed a 90 min soccer-specific protocol on three occasions. Either 3 ml/kg body mass of a solution containing glucose (1 g/min glucose) (GLU), or glucose (0.66 g · min-1) plus fructose (0.33 g · min-1) (MIX) or placebo (PLA) was consumed every 15 minutes. Respiratory measures were undertaken at 15-min intervals, blood samples were drawn at rest, half-time and on completion of the protocol, and muscle glycogen concentration was assessed pre- and post-exercise. Following the soccer-specific protocol the Cunningham and Faulkner test was performed. No significant differences in post-exercise muscle glycogen concentration (PLA, 62.99 ± 8.39 mmol · kg wet weight-1; GLU 68.62 ± 2.70; mmol · kg wet weight-1 and MIX 76.63 ± 6.92 mmol · kg wet weight-1) or exercise capacity (PLA, 73.62 ± 8.61 s; GLU, 77.11 ± 7.17 s; MIX, 83.04 ± 9.65 s) were observed between treatments (P > 0.05). However, total carbohydrate oxidation was significantly increased during MIX compared with PLA (P < 0.05). These results suggest that when ingested in moderate amounts, the type of carbohydrate does not influence metabolism during soccer-specific intermittent exercise or affect performance capacity after exercise in the heat.